Fraud in a digital society in the context of social change - A. Yu. Sergeyev; O. V. Shirokova (Цифровая социология, 2023)
The article analyzes the problems of fraud in the modern digital society in the context of social changes caused by both the COVID-19 pandemic and the current geopolitical situation. The authors study in detail the types of financial fraud in this area. They pay special attention to the types of digital fraud: telephone fraud and IP-telephony, SMS fraud, phishing, sniffering (message interception), skimming (theft of card data), which are associated with the emergence of cryptocurrencies. The article presents the data of the authors’ sociological research conducted by the method of an online questionnaire survey (n = 765). The study showed that only 44 % of respondents are sufficiently informed about the types of fraud to protect themselves from modern internet scammers. An analysis of data on certain types of digital fraud showed that 20 % of respondents lost money due to telephone or Internet fraud, 16 % of respondents personally encountered IP telephony, and 40 % have no idea about such a type of fraud as sniffering and existing anti-virus protection against it. The research also showed the vulnerability, first of all, of the male half of the population over 40 years of age in the field of internet fraud. Therefore, public authorities, together with the media, business and other actors of Russian society, need to strengthen the policy in the field of improving the level of financial and digital literacy of the population.